Structural basis to identify a target site in Shiga toxin for the inhibitor discovery against growth of Shiga toxin-producing E. coli - Anuja Prabhudesai; Samir Shaikh; Kayasth Zarna Ashwinbhai; Reeshu Gupta (Bulletin of the National Research Centre, 2024)
Abstract Background Certain peptides that bind Shiga toxin 2 (Stx2) have been reported to treat Shiga toxin-producing Escherichia coli (STEC) infections. However, their mechanisms of action remain unknown. STEC infections lead to serious diseases, such as hemolytic uremic syndrome, in humans. Antibiotic therapy is usually not recommended because of the major challenges of antibiotic resistance and SOS repair. Currently, there is no human vaccine for STEC infection, leaving rehydration therapy as the recommended supportive therapy. Therefore, there is a need for targeted therapeutic intervention to inhibit STEC growth. The purpose of this study was to evaluate the interaction of five known peptides with Stx2 to identify a more suitable peptide based on structural changes. These peptides have been used to inhibit the growth of STEC. Results The current study demonstrated that only tetravalent peptide (TVP) out of 5 common peptides interrupted the Y77-E259 interaction of Stx2, making it active by exposing active site, which ultimately leads to STEC cell death. We also demonstrated that amino acids R170 and F171 of Stx2 in the docked complex of Stx2 and TVP form a helix-loop-helix (HLH). This might lead to the differential expression of genes regulated by Stx2 and ultimately inhibit STEC growth. However, in the case of Stx2-ribosomal P-stalk, these residues did not form HLH. The 3D refined model of TVP showed a low MolProbity score and low energy zones in the ANOLEA profile compared to the original one. Moreover, the low radius of gyration of the refined TVP suggests that it is more compact than the original TVP. Therefore, TVP is a suitable drug candidate for the inhibition of STEC growth. However, the low antigenicity of TVP makes it unsuitable as a drug candidate. We also evaluated three antibiotics that have been used as active ingredients in FDA-approved peptides. Only Oritavancin diphosphate showed strong polar interactions with Y77-E259 and also had the highest binding affinity. Conclusions Potential drug candidates that inhibit or interrupt the interaction between Y77-E259 and have high antigenicity, low toxicity, and no allergenicity should be explored against the growth of STEC.